SLC25A21 Suppresses Cell Growth in Bladder Cancer via an Oxidative Stress-Mediated Mechanism - Wang, Yong; Gao, Jiawen; Hu, Shasha; Zeng, Weiting; Yang, Hongjun; Chen, Hui; Wang, Shuang (Frontiers in Oncology, 2021)
Background: Bladder cancer (BCa) is a commonly diagnosed malignancy worldwide that has poor survival depending on its intrinsic biologic aggressiveness and a peculiar radio- and chemoresistance features. Gaining a better understanding of tumorigenesis and developing new diagnosis and treatment strategies for BCa is important for improving BCa clinical outcome. SLC25 family member 21 (SLC25A21), a carrier transporting C5-C7 oxodicarboxylates, has been reported to contribute to oxoadipate acidemia. However, the potential role of SLC25A21 in cancer remains absolutely unknown. Methods: The expression levels of SLC25A21 in BCa and normal tissues were examined by real-time PCR and immunohistochemistry. Gain-of- and loss-of-function experiments were performed to detect the biological functions of SLC25A21 in vitro and in vivo by CCK-8 assay, plate colony formation assay, cell migration, invasion assay and experimental animal models. The subcellular distribution of substrate mediated by SLC25A21, mitochondrial membrane potential and ROS production were assessed to explore the potential mechanism of SLC25A21 in BCa. Results: We found that the expression of SLC25A21 was downregulated in BCa tissues compared to normal tissues. A significant positive correlation between decreased SLC25A21 expression and poor prognosis was observed in BCa patients. Overexpression of SLC25A21 significantly inhibited cell proliferation, migration and invasion and induced apoptosis in vitro. Moreover, the enhanced SLC25A21 expression significantly suppressed tumor growth in a xenograft mouse model. Furthermore, we revealed that SLC25A21 suppressed BCa growth by inducing the efflux of mitochondrial α-KG to the cytosol, decreasing to against oxidative stress, and activating the ROS-mediated mitochondrion-dependent apoptosis pathway. Conclusions: Our findings provide the first link between SLC25A21 expression and BCa and demonstrate that SLC25A21 acts as a crucial suppressor in BCa progression, which may help to provide new targets for BCa intervention.